POSITIONS OF NON-VIOLENCE AND NON-INTERFERENCE IN STUDENTS: COMPARATIVE ANALYSIS - V. G. Maralov; V. A. Sitarov (Russian State Vocational Pedagogical University, 2019)
Introduction. The ability to non-violent interaction acts as the most important indicator of professional competency of specialists of "person to person" type occupations: teachers, psychologists, physicians, social workers, etc. Such ability has to be formed at the stage of higher education institution. To build the conditions for development and consolidation in students of the position of non-violence and to neutralise propensity to coercion and manipulation, it is necessary to provide regular monitoring on the identification of prevalent psychological attitudes in students: coercion, manipulation, non-violence, non-interference, including the analysis of their structure and content. However, correctional work with students can become complicated by their internal resistance to the need to change personally, overcoming the developed stereotypes and attitudes, as well as by ambiguity of potential deformations of positions similar to non-violence, but not similar to its positions.The aim of the present research consisted in comparative characteristic of positions of non-violence and non-interference in students of psycho-pedagogical and medical specialties.Methodology and research methods. The methodological framework of the research was based on the provisions of modern philosophy, pedagogics and psychology about non-violence as a universal human value. As a diagnostic tool, the authors designed the questionnaires to identify the types of students' interaction with people and the positions held by students. The tests of "Motivation to Success" and "Motivation of Failure Avoidance" by T. Ehlers, the test-questionnaire "Readiness for risk" by G. Schubert, "Method for Studying Trust to Own Self" by N. B. Astanina were employed. The total sample involved 362 students of the Moscow University for the Humanities, Cherepovets State University and Ivanovo State Medical Academy. To conduct the comparative analysis, the groups of students with the expressed non-violence position - 81 persons (22.38% of the total sample) and students with the expressed non-interference position - 34 persons (9.39% of the total sample) were allocated. The statistical significance of distinctions was calculated using of the Fisher's angular transformation. Results and scientific novelty. As a result, it was established that a low level of irritability to people, high sensitivity to people, moderate expressiveness of motivation of success achievement and readiness to take the reasonable risk are common to students with prevalence of the position of non-violence. The respondents of this group demonstrated the dominant need for safety, which is expressed in high sensitivity to threats and choice of adequate ways of reaction in life-threatening situations with the average level of own credibility. The higher potential of irritability, low sensitivity to other people, tendency to failures avoiding and desire not to risk prevail among the students with the expressed position of non-interference. The need for experience of feeling safety, low sensitivity to threats, the aspiration to exaggerate value of dangers and low level of own credibility characterise the students of the group described above. The authors concluded that sensitivity to another person and own credibility act as the key factors, which cause the acceptance by students of the positions of non-violence or non-interference.Practical significance. The received results can be used in the course of formation of students' ability to non-violent interaction as the most important professional competency of future specialists of "person to person" type occupations.